Strengthening Character Through Pancasila Student Profiles: Impact and Challenges in Learning at SDN 02 Amban - Madada, Nelwan; Ihsan, Ihsan; Faizin, Muhammad; Simatupang, Ernawati (PrimaryEdu : Journal of Primary Education, 2025)
This research aims to explore the implementation of the Pancasila Student Profile (PPP) at SDN 02 Amban, South Sorong Regency, Southwest Papua, as well as the impacts and challenges faced in strengthening student character. Character education based on Pancasila values ​​is very relevant in Papua, taking into account the cultural diversity and geographical challenges that exist. The method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews and document analysis. The research results show that the implementation of PPP at SDN 02 Amban succeeded in integrating Pancasila values ​​such as mutual cooperation, social justice and humanity in learning. However, challenges such as limited teacher training, inadequate infrastructure, and lack of parent participation in character education are the main obstacles. This research suggests the need for increased teacher training, a greater role for parents, and improved infrastructure to support more effective PPP implementation.